A comparative analysis of volatile organic compounds in Paeoniae Radix Alba processed using different methods - Liu, Yuqing; Du, Yafang; Xiao, Yadan; Wu, Yue; Huang, Dan; Guo, Xuan (Frontiers in Nutrition, 2025)
IntroductionPaeoniae Radix Alba (PRA) is a popular functional food, and volatile organic compounds (VOCs) are a critical aspect of PRA. Different processing methods often have a certain impact on VOCs.MethodsTo investigate which VOCs have changed due to different processing methods, this study utilized gas chromatography–ion mobility spectrometry (GC-IMS), the Heracles NEO ultra-fast gas phase electronic nose (E-nose), and chemometric methods to compare and analyze the VOCs in PRA subjected to different processing methods: PRA (prepared slices, stir-baked, stir-baked with bran and stir-baked with wine).ResultsA total of 85 VOCs were detected. Chemometric methods such as principal component analysis (PCA), cluster analysis (CA), and partial least squares regression analysis (PLS-DA) revealed that different processing methods have a significant impact on the VOCs of PRA. Among the PRA samples subjected to the three processing methods, the difference between PRA (prepared slices) and PRA (stir-baked with wine) is the largest. A higher amount of linalool oxide, is present in PRA (prepared slices) than in the other groups. The content of propanoic acid is highest in PRA (stir-baked with wine).DiscussionThe differences in VOCs between PRA (stir-baked) and PRA (stir-baked with bran) are small. This study provides a theoretical basis for the development and clinical scientific application of functional foods related to PRA in the future.